Legal Protection of the Status and Rights of Biological Children (Case Study of Determination Number 114/Pdt.P/2025/Pa.Bi) - Salsabila Khairunnisa; Burhanudin Harahap; Arsyad Aldyan (Rechtsvinding, 2026)
This study aims to analyze the legal protection of the status and rights of biological children according to Islamic law and the Child Protection Law, especially in assessing the suitability of the judge's legal considerations in Determination Number 114/Pdt.P/2025/PA. Bi to the principles of child justice and the fulfillment of civil rights without burdening children due to parental errors. The method used is normative juridical by examining Islamic legal norms through sharia maqasid and national laws and regulations, through literature studies on primary legal materials in the form of court decisions and secondary, analyzed qualitatively with normative interpretation. The results of the study show that Islamic law places biological children as a divine mandate that is protected by nasab for the sake of hifz al-nasl, even though the legal status is limited to sharia marriage so that the right of inheritance of faraidh does not fully apply to children of serial polygamy as in the case of Determination 114/Pdt.P/2025/PA. However, the rights to alimony, education, and affection must still be fulfilled by the father reasonably to be independent; The Child Protection Law guarantees the right to identity, health, and participation without discrimination through a complete birth certificate after biological attestation via DNA test, although judges' considerations often limit legal status due to administrative violations of parental marriage, so that children only receive partial rights such as alimony through a district court lawsuit without full guardianship or inheritance priority, which has the potential to cause social stigmatization and difficulty accessing public services such as scholarships or BPJS in areas such as Kediri; This gap creates a subjective injustice because the child is innocent, as the Constitutional Court's Decision expands biological civil relations in the best interests of the child, but the implementation of religious courts is still formalistic so that optimal protection requires harmonization through progressive fatwas and restorative mediation to ensure family reintegration and long-term psychological stability of children.